The Grass Ceiling: Hidden Educational Barriers in Rural England - Luke Graham (Education Sciences, 2024)
Rurality is rarely integrated into analyses of educational inequalities and this article presents an alternative perspective on rural–urban attainment and highlights the impact of rurality on educational outcomes. The traditional narrative of urban–rural educational disadvantage is that urban pupils do less well in the English exam system. Decontextualised data across different English exam performance measures demonstrate how rural pupils outperform their urban counterparts. Socioeconomic disadvantage (SED) has the most significant impact on attainment and this analysis explores the rural–urban attainment gap through this SED lens. An analysis of the Department for Education (DfE) data explores possible factors that might explain the emerging rural educational gap and presents an argument that rurality is another limiting factor that intersects with SED. This article demonstrates how rural underachievement in England has been hidden by the relative sizes and SED distribution of rural and urban populations.